Evaluation of Benzene Threshold Value in Benzene Exposed Work Environment: Case Study at Ciputat Gas Station - Shinta Arta Mulia1, Zikri Fathur Rahman1, Ahmad Muslih Bambang Sugiharta1, Lili Susanti1, Abdul Rohi (Indian Journal of Forensic Medicine & Toxicology, 2020)
Benzene is dangerous chemical compounds from products General Fuel Filling stations (gas stations) and is one component in gasoline with 1-5% carcinogen content. The purpose of this study was to determine the limits of safe concentration for benzene in the work environment of gas stations in Ciputat. This type of research is an observational, cross-sectional and descriptive study. The population in this study were all workers at one gas station in the Ciputat region. The sampling technique is the total population, so the sample is 27 workers. The design of the study begins with the collection of secondary data related to work processes which include chemicals in the work area and the number of workers involved. Furthermore, primary data collection was carried out related to the concentration of benzene in the workplace air, length of work time, and worker weight. In addition, secondary data was collected in experimental animals, namely the weight of white mice. The type of data in this study is primary data, obtained through questionnaires and observations as well as measurements of benzene in the air of the respondent’s workplace.The measurement results of the concentration of benzene in the gas station in Ciputat in point 1 and point 2 are 0.58 mg / m3 or 0.18 ppm so that the concentration is still below the Threshold Value (TLV) according to Minister of Manpower Regulation Number 5 of 2018. Based on the manual calculation for safe limits of benzene concentration obtained 0.085 mg / m3 or 0.026 ppm. Control recommendations are to consume the CYP2E1 enzyme contained in beef liver and salmon which serves to reduce the level of benzene in the body, use the appropriate Personal Protective Equipment (PPE) in the form of half mask respirator with an organic vapor cartridge, and plant a number of ornamental plants that can absorb and reduce benzene concentrations such as Boston and Golden Photos 1